Biological activity of some essential oil constituents in four Nepeta L. species against Sitophilus oryzae L. - SHAHLA AMINI; MAJID GHORBANI NOHOOJI; MOUSA KHANI; MOHAMMAD REZA LABBAFI; FARAHNAZ KHALIGHI-SIGAROODI (Biodiversitas Journal of Biological Diversity, 2019)
Amini S, Nohooji MG, Khani M, Labbafi MR, Khalighi-Sigaroodi f. 2019. Biological activity of some essential oil constituents in four Nepeta L. species against Sitophilus oryzae L.. Biodiversitas 20: 338-343. Recently, there has been a growing interest in research concerning the possible use of plant extracts as alternatives to synthetic insecticides. Essential oils are among the best-known natural substances with insecticidal properties. These compounds may act as fumigants, contact insecticides, repellents, antifeedants and may affect growth and development of the insects. In an attempt to find a natural and inexpensive method for the control of stored-product pests, contact toxicity of essential oils of Nepeta cataria, Nepeta pogonosperma, Nepeta glomerulosa. and Nepeta binaloudensis. were investigated on adult insects of Sitophilus oryzae L. (Coleoptera, Curculionidae) in vitro condition. Chemical Composition, repellency and fumigant toxicity of the essential oils were investigated. Chemical composition of the essential oils of above plants were identified by GC-MS. 4a?,7?,7a?-nepetalactone (82.74 %) was major component of N. cataria and also different isomers of nepetalactone were among the major compounds in N. Pogonosperma and N. binaloudensis oils. In fumigants bioassay, N. glomerulosa (124.318?L/L air) showed the highest toxicity against S. oryzae adults, followed by N.pogonosperma (150.49?L/L air) and N. cataria (152.630?L/L air), respectively. Also, the S. oryzae was repelled by N. cataria (91.61%) and N. binaloudensis (91.50 %), respectively.